Psychotropic medication use among elderly nursing home residents in Slovenia: cross-sectional study - Petek Šter, Marija (Croatian Medical Schools, 2011)
AIM: To determine the prevalence of psychotropic medication prescribing in elderly nursing home residents in Slovenia and to explore the residents’, physicians’, and nursing home characteristics associated with prescribing. METHODS: In a cross-sectional study, we collected the data for 2040 nursing home residents aged 65 years and older in 12 nursing homes in Slovenia between September 25 and November 30, 2006. Prescribed medications lists were retrieved from patients’ medical records. Psychotropic medications were coded according to Anatomical Therapeutic Chemical Classification 2005, which we adjusted for the purposes of the study. Multivariate logistic regression analysis was performed to determine the residents’, physicians’, and nursing home characteristics associated with prescribing. RESULTS: Residents were from 65 to 104 years old (median, 83 years) and 1606 (79%) of them were female. A total of 970 (48%) residents had dementia and 466 had depression (23%). In 1492 (73%) residents, at least one psychotropic medication was prescribed. Nine hundred sixty residents were prescribed hypnotics and sedatives (47%), 572 (28%) antipsychotics, 460 (23%) antidepressants, and 432 (21%) anxiolytics. Residents’ characteristics associated with psychotropic medication use were female sex (odds ratio [OR], 1.36; 95% confidence interval [CI], 1.03-1.80), age (OR, 0.97; 95% CI, 0.95-0.98), permanent restlessness (OR, 2.54; 95% CI, 1.71-3.78), dementia (OR, 1.76; 95% CI, 1.33-2.34), depression (OR, 5.51; 95% CI, 3.50-7.58), and the number of prescribed medications (OR, 1.29; 95% CI, 1.23-1.35). Of physicians’ characteristics (sex, age, specialization in general practice, years of working experiences as a general practitioner, and years of experiences working in a nursing home), male sex was associated with psychotropic medication prescribing (OR, 1.80; 95% CI, 1.17-2.76). CONCLUSION: Frequency of psychotropic medication prescribing in elderly nursing home residents in Slovenia is high and is comparable to Western European countries. Our next step should be optimizing the prescribing in patients with the highest prescription rate.